International human resource management - Harzing, Anne-Wil (SAGE, 2011)
Previous ed.: 2004; Includes bibliographical references and index; The eagerly-awaited third edition of the hugely successful International Human Resource Management succeeds in maintaining the academic rigour and critical focus that have established its reputation as the most authoritative and cutting-edge text in the field